Pengalaman Tamu Mengenai Housekeeping dan Fasilitas di TRC Bintan Resort - Melisa Sri Dewi; Nensi Lapotulo; I Wayan Thariqy Kawakibi Pristiwasa; Yudha Wardani (Journal of Tourism and Economic, 2025)
This study examines the negative experiences of guests staying at TRC Bintan Resort, focusing on the quality of basic services and the physical condition of the property. The analysis was conducted using a descriptive qualitative approach, based on a narrative review of online reviews containing complaints about room sanitation, infrastructure damage, and environmental discomfort. The results revealed systemic failures, including weak hygiene standards, facility degradation, and inadequate management of the resort environment, which directly impacted guest perceptions of value and emotions. These findings reinforce the existence of a total quality gap arising from the mismatch between guest expectations and service realities. Using the SERVQUAL framework and the Kano Model, this study identified that most issues centred on the basic needs dimension, which must be met in the hospitality industry. This study contributes to the hospitality management literature by highlighting the importance of preventative maintenance, service quality monitoring, and the integration of environmental sustainability principles as strategies for rehabilitating resort reputations in tropical coastal areas.